BEHAVIOR ANALYSIS OF PROFITABILITY IN DECISION MAKING IN RUMAH SAKIT UMUM. - Miranti Puspaningtyas (AIBPM Publisher, 2019)
The purpose of this study is to find out how information profitability in helping managers make decisions and how the behavior shown when making decisions. This study uses a qualitative phenomenological approach to look at decision-making behavior. The research findings show that there are uncertainties in financial reporting because of changes in the financial recording system from the cash basis to accrual basis. The findings also show that in decision-making, there is still impact of ego and the tendency to choose decisions based on intuition by decision makers. Related to behavioral aspects, it is better to make decisions that need observes the conditions of the entity and equalize between id, ego, and super ego, too. The implications of this study found some consequences of the uncertainty of financial statements for changes in the financial recording system that have an impact on decision-making behavior preferences.